Study on Stability Control of Gob-Side Entry Retaining Structure Without Filling Wall in Hard Roof - Jing-kui, Long; Chao-xin, Qi; Zuo-yong, Cao; Hong, Lan; Wen-kai, Yu (Frontiers in Earth Science, 2022)
In view of the deformation and instability law of hard roof without side filling retaining roadway, based on the systematic construction and analysis of the force and bearing model of roadway retaining structure, this article proposes the control mechanical model and calculation method of roadway retaining, which takes the anchor roof beam and the key block above to form the cantilever beam together, with the anchor solid coal side as the foundation support. The research and practice show that under the condition of hard roof, the mechanical connection between the roof of gob-side entry retaining and the roof of mining face can be effectively cut off so as to improve the structural configuration and mechanical properties of the lateral roof of gob-side entry retaining and the key blocks above, and reduce the damage of upper strata subsidence and goaf roof collapse to the roof of roadway. Then, through strengthening by anchor to significantly enhance solid coal side, bearing capacity of anchor roof beam, so they can share the upper strata caused by the load and deflection of mining influence, in addition, the roof bolting, reinforcement of waste rock bolting supporting role can better improve the structure for stability, adaptability and engineering applicability, this method is successfully applied in engineering practice. It is worthy of further research and application.